The Portuguese Appeasement Policy in Macau's Church and State Relations - Leung, Beatrice (The Journal of contemporary China, 2010)
For the last four centuries, under the policy of the Portuguese Padroado1454, the Macau Catholic Church has been closely associated with the Portuguese rulers of Macau in governing this 'Chinese territory under the Portuguese rule'. This church-state relationship in Macau before the Chinese takeover (1999) and after has become a client-patron relationship under the shadow of the Portuguese appeasement policy. In the context of the appeasement policy, this paper aims at discussing: (1) the close alliance between the Portuguese government and the Catholic Church in Macau, offering special privileges and convenience to the Church but weakening church capacity in evangelization and spiritual leadership; and (2) the interactions of the three actors in the triangular relationship among the Vatican, China and Macau.
URL under conditioned access. Contact USJ Library